The World Bank Group A to Z - WorldBankGroup (World Bank, 2015)
The World Bank Group A to Z provides the most concise and essential information about the mission, policies, procedures, products, and services of the new World Bank Group. With more than 280 entries arranged in encyclopedic A-to-Z format, readers can easily find up-to-date information about the five agencies of the World Bank Group and the wide range of areas in which they work: from agriculture, education, energy, health, social protection, and labor to gender, jobs, conflict, private sector development, trade, water, and climate change. The World Bank Group?s work in all of these areas now focuses on two new twin goals: eliminating extreme poverty by 2030 and boosting shared prosperity of the poorest 40 percent in every developing country.